Analysis of the effectiveness of regulatory legal acts on counterfeiting of medicines in Ukraine - S. O. Lebed; A. S. Nemchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The problem of medicines counterfeiting is relevant for all countries of the world, without exception. At the same time, the effectiveness of combating the spread of counterfeit medicines (CM) in different countries, as well as the volume of counterfeited medical products, varies. Any state that aimed to ensure highly effective control over the circulation of medicines has to elaborate a comprehensive solution to this problem, primarily to adopt high-quality national legislation. The executive authorities should not only pay attention to neutralizing CM problem, but also take the most active part in this process. The primary role here should be played by law enforcement authorities. There is a need for coordinated work by law enforcement authorities to investigate the cases of falsified medicines and clandestine production, as well as by regulatory bodies to identify such products. It is also necessary to systematize the investigative and judicial practice on this issue, create an unified system for recording the facts of identifying the counterfeit drugs. The need for systematic monitoring and analysis of regulatory legal acts regarding the counteraction to the circulation of the CM in order to assess their effectiveness, as well as the adoption of appropriate measures by the authorized bodies, determine the relevance of the study.